Preliminary assessment criteria for prescribing exercise when treating eating disorders: What do the experts have to say?. (October 2018) - Quesnel, Danika A.; Libben, Maya; Caperchione, Cristina M.
Highlights: A qualitative study of ED experts offering health parameters warranting consideration if including exercise in ED treatment. The outlined parameters include aspects of mental and physical health, nutrition and exercise behaviours. Results suggest ways to assess if and when an individual may safely and healthfully engage in exercise during ED treatment.